Relationship between economic indicators towards company performance: study of CTAPPS MSC Sdn Bhd / Sarila Osman - Osman, Sarila (2011)
The main objective of this paper is to examine the relationships between economic indicators represented by gross domestic product, consumer price index and unemployment rate towards company performance. Also to determine the extent to which GDP, CPI and unemployment rate influenced performance of that organization in order to survive in any economic situations. The finding has been evaluated by using eviews version 7 and it shown that only unemployment rate has significant relationship towards company performance while GDP and CPI have no relationship. This relationship has been measured by t-test statistic with the probability 0.03 which means unemployment rate have significant relationship with 95% level of confidence or significant. However it may vary between industries since CTAPPS MSC only engaged in IT industries.